Factors affecting parathyroid hormone levels in different types of primary aldosteronism. (2nd February 2016) - Jiang, Yiran; Zhang, Cui; Ye, Lei; Su, Tingwei; Zhou, Weiwei; Jiang, Lei; Zhang, Yifei; Wang, Weiqing
Summary: Background: Recent studies have found that mild secondary hyperparathyroidism might be another clinical feature of patients with primary aldosteronims (PA), but whether serum parathyroid hormone level (PTH) is correlated with subtypes of PA and what contributes to the elevated PTH level remains unclear. Objective: To illustrate the changes of PTH in PA and to partly explain the mechanism of how the effects of aldosterone regulating the secretion of PTH in PA. Methods: We enrolled a total of 120 patients with primary hypertension (PH) and 242 patients with PA, which included 89 APAs (aldosterone‐producing adenoma), 119 IHAs (idiopathic hyperaldosteronism) and 34 UAHs (unilateral adrenal hyperplasia). The plasma levels of aldosterone, renin activity, parathyroid hormone and markers associated with calcium metabolism were measured. Results: We found serum PTH level was significantly elevated in patients with PA compared with primary hypertension [9·0 (6·6, 11·7) vs 5·7 (4·4, 7·0)] pmol/l, P < 0·001]. However, no difference was found between the three PA subtypes ( P > 0·05). Stepwise multiple regression analysis showed that in patients with PA, serum levels of K + and Ca 2+ were independently associated with serum PTH level. More importantly, elevated PTH level could be corrected either by unilateral adrenalectomy [9·9 (7·5, 12·8) vs 5·2 (4·4, 7·0) pmol/l, P < 0·001] or mineralocorticoid receptor (MR) antagonists treatment [11·7 (9·1, 13·4) vs 6·3 (5·1, 7·8) pmol/l, P < 0·001]. Conclusions: PTH level is elevated in PA patients and irrelevant with subtypes of PA. Serum K + and serum Ca 2+ level are main factors influence the plasma PTH level in PA patients. After medical or surgical treatment, PTH levels return to normal.